FATIGUE LIFE ANALYSIS OF SIMULATED AIRCRAFT BEAM STRUCTURE CONNECTION - ZHENG Jie; LIU Yang; TONG MingBo (Jixie qiangdu)
Experimental and simulation methods were used to predict the fatigue life of the connecting part of the aircraft beam structure. First of all,based on the statistical analysis,the marker load was chosen. The experimental results show that the marker load method can quantitatively record the initiation and propagation of cracks. Meanwhile this paper established a finite element model of the three-dimensional connection part of aircraft beam structure,with soft-soft contact and pre-stressing force modal. The errors between the results of the finite element model and the static experimental results are within 10%. Finally,with the help of the local stress-strain method and the software FEMFAT,the fatigue life of the test specimens was successfully predicted. The two results were compared to each other. It is find out that the crack formation time generated by the local stressstrain method is radical,while the FEMFAT software can obtain a conservative crack formation time which is consistent with the test results.